2017
DOI: 10.20883/jms.2017.206
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of the elderly residents of nursing homes and patients of the Psychogeriatric Day Ward

Abstract: IntroductionAccording to the offi cial forecasts the population of people aged 65 and over in the European Union will increase from 87.5 million in 2010 to 152.6 million in 2060. There are also predictions of the number of persons aged 80 and above growing from 23.7 million in 2010 to 62.4 million in 2060 [1]. Designing and implementing measures aimed at improving the quality of such extended life is one of the challenges facing medicine today.Quality of life (QoL) is a multi-dimensional and interdisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In studies assessing quality of life using the WHOQOL questionnaire, elderly patients would usually score more than 60 points which is above a good score [ 3 6 , 18 , 27 ]. In our studies, the score varied from 51 to 60 points.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies assessing quality of life using the WHOQOL questionnaire, elderly patients would usually score more than 60 points which is above a good score [ 3 6 , 18 , 27 ]. In our studies, the score varied from 51 to 60 points.…”
Section: Discussionmentioning
confidence: 99%
“…Greater differences were found in the assessment of the domain deemed to be the most satisfactory. Researchers usually indicate the domain of Social relationships [ 2 , 10 , 24 ] or the Environment domain [ 5 , 18 , 27 ]. Studies conducted in the United States have shown that poorer ability in activities of daily living, memory disorders and depression, and greater number of comorbidities were associated with a lower quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La Organización Mundial de la Salud (OMS) define la calidad de vida como "la percepción que tiene un individuo de su posición en la vida, en el contexto de la cultura y los sistemas de valores en los que vive y en relación con sus metas, expectativas, estándares e inquietudes" (2) . En los AM la CV depende de la salud biológica, y del buen funcionamiento mental, social, cultural, y espiritual (3) .…”
Section: Introductionunclassified